Determinants of worker participation in basic occupational health services: The roles of social capital and motivation among informal tourism workers in Indonesia - Agustin, Helfi; Akhyar, Muhammad; Sumardiyono; Habsari, Sri Kusumo (International Journal of Occupational Safety and Health, 2026)
Introduction: Informal tourism workers play a vital role in Indonesia’s tourism economy but often lack access to occupational health protections, making them vulnerable to workplace hazards. Basic Occupational Health Services (BOHS) provide a preventive and promotive health framework for underserved sectors; however, participation among informal workers remains limited and the determinants of readiness to engage in BOHS are still poorly understood.Methods: A cross-sectional survey was conducted among 222 informal tourism workers in Yogyakarta, Indonesia. Data were collected using validated questionnaires and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) to examine the relationships among health promotion, social capital, motivation, and readiness to participate in BOHS.Results: Social capital exerted the strongest influence on health promotion (β = 0.667, p < 0.001) and significantly affected motivation (β = 0.273, p = 0.003) and readiness to participate (β = 0.234, p = 0.001). Health promotion significantly predicted motivation (β = 0.240, p = 0.004) and readiness (β = 0.360, p < 0.001). Motivation partially mediated the effects of both social capital and health promotion on readiness. The model demonstrated moderate to substantial explanatory power (R² readiness = 0.534) and good predictive relevance (Q² readiness = 0.283).Conclusion: Strengthening BOHS participation among informal tourism workers requires strategies that enhance community social capital and motivational engagement rather than relying solely on information dissemination. Participatory health promotion and community-based initiatives may improve readiness and sustainability of BOHS programmes in informal tourism settings.